Prospects of solar electric power systems in rural Malaysia - Endan, Johari; Bardaie, Mohd. Zohadie (1982)
Rural electrification by extension lines bears a high cost and is difficult to implement due to various administrative and social problems. Solar electric power can meet a large variety of small-scale decentralised energy needs and solve most of the problems mentioned above. Most of the energy needs can be provided by photovoltaic systems and in wind prevailing areas combined systems with photovoltaics and wind engines. Photovoltaics can be used to pump water, run fans for solar dryers, power telephone and signal service systems, provide household power units or a communal recreation center, etc. Wind engines can be used for direct driving of mechanical equipment like water pumps, mills, etc., or for electrical energy generation. Proposal on the types of systems and its adaptability to the Malaysian rural areas is made. It is envisaged that the price of photovoltaics and other solar electrical power systems would decrease with advancement in technology and automation so as to upset the costs for conventional electric power systems for rural areas.